2019
DOI: 10.3390/min9020111
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Risk Assessment of Heavy Metals in Sediment from Bohai Bay, China

Abstract: Sediment core and porewater samples from the Western coastal tidal flat in Bohai Bay, China, were collected for meals and physical-chemical properties analysis. The vertical distribution characteristics of eight metals along the core was investigated based on 137Cs and 210Pb radionuclide dating. The chemical fractions of six metals (Cu, Pb, Zn, Ni, Mn and Cd) were also measured based on the modified European Community Bureau of Reference (BCR) sequential extraction procedures to better understand the mobility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 98 publications
(130 reference statements)
0
10
0
Order By: Relevance
“…Tianjin Port, located in Bohai Bay, is the largest comprehensive port in Northern China, where large-scale dredging activities are carried out along the coastal areas every year [34,36]. It was reported that a total of 466 × 104 m 3 of dredged materials were dumped into sites adjacent to the Tianjin Port between 2012 and 2013, resulting in a negative influence on the marine ecosystem in Bohai Bay; therefore, great importance should be attached to this issue [34,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Tianjin Port, located in Bohai Bay, is the largest comprehensive port in Northern China, where large-scale dredging activities are carried out along the coastal areas every year [34,36]. It was reported that a total of 466 × 104 m 3 of dredged materials were dumped into sites adjacent to the Tianjin Port between 2012 and 2013, resulting in a negative influence on the marine ecosystem in Bohai Bay; therefore, great importance should be attached to this issue [34,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…However, information about the fluxes of trace metals at the sediment-water interface in Indonesian waters is still minimal. In other countries, metals flux observations have been carried out, such as in China (Duan et al 2019;Li et al 2020;Liu et al 2019;Ni et al 2017), Sweden (Frogner-Kockum et al 2020, France (Point et al 2007;Rigaud et al 2013), Italy (Emili et al 2016;Zago et al 2000), Spain (Santos-Echeandia et al 2009), Germany (Pohl et al 2004), and the United States (Kalnejais et al 2015). Through the positive or negative signs generated from the flux calculations, we could find out the direction of the metal movement in the sea.…”
Section: Studies On Trace Metals In Indonesian Watersmentioning
confidence: 99%
“…Fluxes of dissolved metals between porewater sediment and overlying bottom water are driven by different concentrations in chemical composition on both sides (Berner 1976). The concentration gradient at the sedimentwater interface is used to calculate the outward flux from the sediment or inward flux to the sediment (Liu et al 2019). When metal concentrations in the uppermost porewater is higher compared with the dissolved metal concentrations in bottom seawater, it indicates that the benthic flux of metals will be released by sediments to overlying waters (Li et al 2020;Zhu et al 2016).…”
Section: Sediment Porewater Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Tianjin Port, located in Bohai Bay, is the largest comprehensive port in Northern China, where large-scale dredging activities are carried out along the coastal areas annually [34,36]. It was reported that a total of 466×104m 3 of dredged materials were dumped into sites adjacent to the Tianjin Port between 2012 and 2013, resulting in a negative influence on the marine ecosystem in Bohai Bay, and therefore, great importance should be attached to this issue [34,37,38].…”
Section: Introductionmentioning
confidence: 99%